Knowledge, Practice and Factors associated with Utilization of Cervical Cancer Screening Services - Bhattarai, Nancy; Bajracharya, Siddhi Laxmi (Journal of Nepal Health Research Council, 2024)
Background: Cervical cancer is treatable with regular screening and follow-up practices. The utilization of cervical cancer utilization services is found to be unsatisfactory in the context of Nepal. The objective of this study was to assess the factors that influence knowledge, practice, and utilization of cervical cancer screening among women in the Dhulikhel Municipality, Nepal.Methods: A cross-sectional study was conducted on 156 married women residing in Dhulikhel Municipality. The study participants were selected using the convenience sampling method. A standard questionnaire was used to collect the information. This study examined socio-demograhic data, knowledge, practice, and factors associated with cervical cancer screening. Descriptive and inferential statistics were used to analyze the data.Results: Only one-fifth (17.9%) of the participants had received a cervical cancer screening. Most participants possessed a sufficient level, 134 out of 85.9%, of information about cervical cancer and cervical cancer screening. Annual healthcare visits (p=0.00), participant knowledge (p=0.014), and perceived barriers (p=0.001) were statistically significant factors in the uptake of cervical cancer screening. Out of those who felt they were highly susceptible, just one-fourth, or 25%, had undergone cervical cancer screening services.Conclusions: The number of medical visits, participants' knowledge, and perceived barriers had a significant impact on the uptake of cervical cancer screening. However, there was not found any relationship between the use of cervical cancer screening and perceived susceptibility and other socio-demographic factors.Keywords: Cervical cancer; cervical cancer screening; perceived barriers; perceived susceptibility.